EFEKTIVITAS KINERJA KEUANGAN DAN NON KEUANGAN PADA POLA PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH (PPK BLUD)RSUD AMBARAWA KABUPATEN SEMARANG - Yuli Priastuti, Wahyu; Masdjojo, Gregorius Nasiansenus (Proceeding SENDI_U, 2017)
This study aims to determine whether Ambarawa hospital had a level of efficiency and effectiveness both in financial and non-financial performance.This study used secondary data obtained from the financial statements in 2012 through 2014 of Ambarawa Government Hospital. Measurement of financial and non financial performance was governed by Decree of the Minister of Health No. 1164/Menkes/SK/X/2007. We found that the financial performance gained weight value from 2012 to 2014 amounted to 16.7; 18.2 and 18.7. Those indicated that the financial performance of Ambarawa Goverment Hospital as Regional Public Service Institution well. While non-financial performance gained weight value from 2012 to 2014 amounted to 68.25; 73.95 and 74.15. Based on these calculations in the category was HEALTHY AA. Cost calculation recovey Rate (CRR) in 2012 which is 104% continued to rise until 2014 is 143%. This suggests that the hospital was able to support it operations by the revenue it received. As for Level Independence of Ambarawa Goverment Hospital as Regional Public Service Institution in 2012 scored 104% and continues to increase until 2014 at 307%. This shows that as Regional Public Service Institution able to finance operating costs and investment costs, but on the other hand the level of dependence on subsidies from the budget continued to increase from 2012 to 2014. Keywords: Public Service Board, the financial performance indicators and non-financial, recovey Cost Rate (CRR), Level of Independence, efficiency and effectiveness